2016
DOI: 10.1111/asj.12682
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graded levels of liquid brewer's yeast on chemical composition and fermentation quality in cassava pulp and rice straw‐based total mixed ration silage

Abstract: This study aimed to evaluate the effect of liquid brewer's yeast (LBY) addition on chemical composition and fermentation quality of mixture of LBY and cassava pulp (CVP) with rice straw (RS) in different ratios during preservation periods. Four mixtures of LBY, CVP and RS were made, that is mixture ratio of LBY : CVP : RS of 0% LBY, 20% LBY, 35% LBY and 50% LBY were 0:70:30, 20:50:30, 35:35:30 and 50:20:30 as fresh matter, respectively. The bags were opened at weeks 0, 1, 2, 4 and 8 after storage. The contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…The reduced aerobic stability of the silage inoculated with S. cerevisiae alone was mainly due to the high pH value (4.3–4.4) that could not inhibit the growth of aerobic spoilage bacteria after opening. This result is consistent with the outcome of a high pH and poor stability observed by Kamphayae et al [23] when a high proportion of liquid brewer’s yeast was included. In contrast, a lower inoculation dose (10 3 –10 5 cfu/g) of S. cerevisiae did not affect the pH and aerobic stability of corn silage [18,19].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The reduced aerobic stability of the silage inoculated with S. cerevisiae alone was mainly due to the high pH value (4.3–4.4) that could not inhibit the growth of aerobic spoilage bacteria after opening. This result is consistent with the outcome of a high pH and poor stability observed by Kamphayae et al [23] when a high proportion of liquid brewer’s yeast was included. In contrast, a lower inoculation dose (10 3 –10 5 cfu/g) of S. cerevisiae did not affect the pH and aerobic stability of corn silage [18,19].…”
Section: Discussionsupporting
confidence: 92%
“…This inconsistency is possibly due to the difference in application dose of S. cerevisiae . Additional supportive evidence is provided by Kamphayae et al [23], who observed an increase in pH when the proportion of liquid brewer’s yeast included in the mixed silage of cassava pulp and rice straw increased. Thus, for a high inoculation dose of S. cerevisiae , a method by which the ammonia production can be reduced in silage must first be identified.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Cassava ( Manihot esculenta Crantz) pulp is a by‐product of starch manufacturing, and its disposal can cause environmental problems (Napasirth et al., ; Sriroth, et al., ). However, it can be used as a major biomass resource for animal feeding (Kamphayae et al., ). In 2016, 31.16 million tonnes of cassava were produced in Thailand.…”
Section: Introductionmentioning
confidence: 99%